Mutual Interaction of Basophils and T Cells in Chronic Inflammatory Diseases - Sarfati, Marika; Wakahara, Keiko; Chapuy, Laurence; Delespesse, Guy (Frontiers in Immunology, 2015)
Basophils are, together with mast cells, typical innate effector cells of allergen-induced IgE-dependent allergic diseases. Both cell types express the high affinity receptor for IgE (FcεR1), release histamine, inflammatory mediators and cytokines following FcεR1 cross-linking. Basophils are rare granulocytes in blood, lymphoid and non-lymphoid tissues and the difficulties to detect and isolate these cells has hampered the study of their biology and the understanding of their possible role in pathology. Furthermore, the existence of other FcεR1-expressing cells, including professional Ag-presenting dendritic cells, generated some controversy regarding the ability of basophils to express MHC Class II molecules, present Ag and drive naïve T cell differentiation into Th2 cells. The focus of this review is to present the recent advances on the interactions between basophils and peripheral blood and tissue memory Th1, Th2 and Th17 cells, as well as their potential role in IgE-independent non allergic chronic inflammatory disorders, including human inflammatory bowel diseases. Basophils interactions with the innate players of IgE-dependent allergic inflammation, particularly innate lymphoid cells, will also be considered. The previously unrecognized function for basophils in skewing adaptive immune responses opens novel perspectives for the understanding of their contribution to the pathogenesis of inflammatory diseases.